Hierarchical NiO–In2O3 microflower (3D)/ nanorod (1D) hetero-architecture as a supercapattery electrode with excellent cyclic stability. Issue 13 (10th March 2016) - Padmanathan, N.; Shao, Han; McNulty, David; O'Dwyer, Colm; Razeeb, Kafil. M.
Abstract : Simultaneous heterogeneous growth of one-dimensional nanorod supported three-dimensional microflower structures on nickel foam enhanced the non-capacitive faradaic energy storage performance due to the synergistic contribution from the hierarchical hybrid nanostructure. Abstract : Three-dimensional (3D) hybrid nanostructured electrodes based on one-dimensional (1D) nanorod arrays have recently attracted great attention owing to their synergistic effect of three-dimensional nanostructures and application in energy storage and conversion devices. Here, we designed a heterostructured supercapattery electrode from a combination of NiO and In2 O3 with a hierarchical hybrid microstructure on nickel foam (NF). Simultaneous heterogeneous growth of 1D nanorod-supported 3D microflower structures on nickel foam enhanced the non-capacitive faradaic energy storage performance due to the synergistic contribution from hierarchical hybrid nanostructure. The heterostructured electrode exhibits a high specific capacity of 766.65 C g −1 at 5 A g −1 and remains as high as 285.12 C g −1 at 30 A g −1 . The composite electrode shows an excellent rate performance as a sandwich type symmetric device, offering a high specific energy of 26.24 W h kg −1 at a high power of 1752.8 W kg −1 . The device shows a long term cyclic stability with 79% retention after 50 000 cycles, which is remarkable for an oxide based pseudocapacitor. These results suggest that NiO–In2 O3 with hybrid micro/nano architecture could be a promising electrode for next generation supercapatteries.